2009
DOI: 10.1598/jaal.53.3.7
|View full text |Cite
|
Sign up to set email alerts
|

e‐Reading and e‐Responding: New Tools for the Next Generation of Readers

Abstract: Contemporary transformations in digital technologies have prompted a reassessment of what literacy means and what is determined a “text.” Traditionally, text has been perceived as written messages and symbols in the forms of books, magazines, and newspapers. Today, text is recognized as much more than written words or images. As teachers consider the need to expand the definition of text to keep up with the evolution of digital technologies, they should remember that today's readers are immersed in multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…For example, Larson's studies of elementary classrooms show how rapidly even second graders begin to use the special features of the e-reader, changing font size, using annotation, etc. (Larson, 2009(Larson, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Larson's studies of elementary classrooms show how rapidly even second graders begin to use the special features of the e-reader, changing font size, using annotation, etc. (Larson, 2009(Larson, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In her small observational study of two second grade students' use of the Kindle, Larson found that the students made use of the adjustable font size, the built-in dictionary to look up and "decode" words, as well as the text to-speech function (p. 19). In an earlier study performed by Larson (2009), she observed ten fifth grade students and their interactions with e-books. The students collectively used the highlighting and note tool features on the Kindle to mark pas sages they wanted to discuss in class or to keep track of plot and characters (Larson, 2009).…”
Section: Cool Tools: a Distraction Or An Aid To Learning?mentioning
confidence: 99%
“…In an earlier study performed by Larson (2009), she observed ten fifth grade students and their interactions with e-books. The students collectively used the highlighting and note tool features on the Kindle to mark pas sages they wanted to discuss in class or to keep track of plot and characters (Larson, 2009). Larson (2009) found that the fifth graders used the note tool to transfer their thoughts onto the device with "spontaneity and impulsiveness," suggesting that they were engaging with the text on a meaningful and per sonal level (p. 256).…”
Section: Cool Tools: a Distraction Or An Aid To Learning?mentioning
confidence: 99%
See 2 more Smart Citations